The expiry of sanctions imposed on legal persons: A comparative analytical study - Hamadache, Chems Eddine (The International tax journal, 2025)
This study addresses the issue of the expiry of criminal sanctions imposed on legal persons. It highlights the distinction between cases where the penalty expires while the conviction remains valid—such as in cases of dissolution, prescription, or special pardon—and those where the conviction and all its effects are completely erased, such as through general amnesty or rehabilitation. The research shows that Algerian legislation does not include specific provisions that regulate the expiry of penalties or the rehabilitation of legal persons. This legislative gap calls for legal intervention to ensure the protection of rights and the establishment of balanced criminal justice